2022
DOI: 10.1093/neuonc/noac263
|View full text |Cite
|
Sign up to set email alerts
|

Trotabresib, an oral potent bromodomain and extraterminal inhibitor, in patients with high-grade gliomas: A phase I, “window-of-opportunity” study

Abstract: Background The bromodomain and extraterminal protein (BET) inhibitor trotabresib has demonstrated antitumor activity in patients with advanced solid tumors, including high-grade gliomas. CC-90010-GBM-001 (NCT04047303) is a phase I study investigating the pharmacokinetics, pharmacodynamics, and CNS penetration of trotabresib in patients with recurrent high-grade gliomas scheduled for salvage resection. Methods Patients receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…These data suggest that trotabresib monotherapy may provide long-lasting disease control in some patients, and demonstrate the long-term efficacy and good tolerability of intermittent dosing of trotabresib even in patients with advanced, progressive disease. Importantly, the durable CR in a patient with progressive diffuse astrocytoma and the minor radiographic response in a patient with high-grade astrocytoma, a tumor type with typically poor outcomes and limited effective treatment options, illustrate the ability of trotabresib to penetrate brain tumor tissue 35 . Penetration of brain tumor tissue is a key challenge in the treatment of gliomas and other central nervous system tumors 36,37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that trotabresib monotherapy may provide long-lasting disease control in some patients, and demonstrate the long-term efficacy and good tolerability of intermittent dosing of trotabresib even in patients with advanced, progressive disease. Importantly, the durable CR in a patient with progressive diffuse astrocytoma and the minor radiographic response in a patient with high-grade astrocytoma, a tumor type with typically poor outcomes and limited effective treatment options, illustrate the ability of trotabresib to penetrate brain tumor tissue 35 . Penetration of brain tumor tissue is a key challenge in the treatment of gliomas and other central nervous system tumors 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…The results reported here demonstrate the preliminary anticancer properties of trotabresib monotherapy across a range of heavily pretreated advanced solid tumors and in R/R DLBCL, supporting further investigation of its use in combination with other anticancer agents. Based on the responses observed in this study, a clinical trial has been initiated to investigate trotabresib in combination with temozolomide in patients with newly diagnosed glioblastoma (NCT04324840) 35,[49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…BALB/c nu/nu ( n = 3) mice bearing U-87 MG subcutaneous tumours were orally administered a therapeutic dose of Trotabresib (25 mg kg −1 ) at 1.5 hours prior to PET imaging and compared to a cohort of non-blocked mice ( n = 3) bearing U-87 MG tumours (Phase I trials of Trotabresib have shown a median time to peak blood concentration of 1.5 hours in patients). 15 A reduction in tumour uptake was observed in cross-sectional PET images of mice pre-administered Trotabresib, relative to non-blocked mice (Fig. 4a and b).…”
mentioning
confidence: 86%
“…14 Currently under Phase II clinical investigations for the treatment of advanced solid tumours (NCT03220347) and glioblastoma as a monotherapy (NCT04047303), and in combination with Temozolomide (NCT03220347) Trotabresib is distinguished from other BET inhibitors by its ability to penetrate the BBB. 15…”
mentioning
confidence: 99%
See 1 more Smart Citation